Low-energy cross-sectional cathodoluminescence analysis of the depth distribution of point defects in Si-ion-implanted β-Ga2O3. (23rd November 2020) - Sugie, Ryuichi; Uchida, Tomoyuki; Hashimoto, Ai; Akahori, Seishi; Matsumura, Koji; Tanii, Yoshiharu
Abstract: Low-energy cross-sectional cathodoluminescence (CL) with a beam energy of 1 keV was applied to Si-ion-implanted β -Ga2 O3 (−201) wafers to investigate implantation damage and recovery. The semi-quantitative CL-intensity depth profiles were obtained by considering nonradiative recombination at the surface. We found that the CL intensity did not fully recover, even after annealing at 1273 K. Such insufficient recovery was prominent in the Si-diffusion region, suggesting that Si-dopant activation and Si diffusion are strongly correlated through interaction with point defects generated by implantation, such as Si interstitials and Ga vacancies.